A CASE OF ACUTE MYOCARDITIS COMPLICATED WITH ATRIAL STANDSTILL AND DIASTOLIC DYSFUNCTION - TANAKA, Kumiko; ISIKAWA, Kou; AKINO, Yoshihisa; SAIRENJI, Hiroshige; SHIDA, Mikio; IKEDA, Shigeaki (Japanese Journal of National Medical Services, 1996)
We report a case of acute myocarditis complicated with atrial standstill and diastolic dysfunction. A 52-year-old woman was admitted to the hospital because of fever, general fatigue and dyspnea. She was diagnosed as having acute myocarditis by the serial changes in ECU and by the increased levels of CPK, GOT and LDH. She was transf erect to our hospital for further examination after congestive heart failure improved. Cardiac catheterization revealed normal systolic function and normal coronary arteries. But the right ventricular pressure trace shoved dip and plateau pattern with an elevated EDP of 18 mmHg. The right atrial pressure trace showed absence of A wave with an elevated mean pressure. Intracardiac electrocardiogram from the RA showed no A wave. The RA did not respond to intracardac electrical stimulation. These findings demonstrated diastolic dysfunction and atrial standstill. As the cause of diastolic dysfunction, constrictive pericarditis must be excluded. After thoracotomy, constrictive pericarditis was ruled out. This case suggests that restrictive cardiomyopathy could develop after acute myocarditis.